Legal Counseling in Increasing Student Awareness Regarding the Impact of Juvenile Delinquency in Sukajati Village, Haurgeulis District, Indramayu Regency - Muhammad Ridzki Fahrudin; M. Agiel Tama P; Tanisah; Widia Andini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Adolescents are the future asset of a nation. However, currently there are a lot of delinquencies in the form of deviations that occur in teenagers. This is a familiar problem. Juvenile delinquency includes all behaviors that deviate from the norms of criminal law committed by adolescents. Delinquency refers to mischievous or rebellious behavior, which is often associated with teenagers or children engaging in activities that are perceived as disobedient or troublesome. These behaviors can range from minor rule violations to more serious acts of defiance against authority or societal norms. There are so many internal and external factors that cause juvenile delinquency that need to be considered. To overcome this, guidance from parents and also a good environment can be a determinant for the development of the adolescent, Therefore, the existence of these problems is planned a work program on Juvenile Delinquency which is held at SMPN 1 Haurgeulis. Juvenile delinquency is commonly referred to as juvenile delinguency. Juvenile comes from the Latin word Juvenilis which means children, young people, while delinguency comes from the Latin delinquere which means neglect, neglect, which then becomes a deviant act/evil. Juvenile delinquency includes all behaviors that deviate from the norms of criminal law committed by adolescents. This behavior will harm yourself and the people around you. The purpose of holding this counseling is to provide knowledge to the community, especially the students of SMPN 1 Haurgeulis so that they can have an understanding of efforts to overcome juvenile delinquency and how to prevent it. juvenile delinquency behavior that can harm them and the surrounding community. The delivery method used is in the form of counseling to adolescents in schools and the community of Sukajati Village, especially adolescents in Sukajati Village about the prevention of juvenile delinquency in accordance with the applicable laws and regulations. In the research, the data used is a quantitative method because this study intends to provide information and prevention efforts to adolescents at SMPN 1 Haurgeulis. After all the data has been collected, the next step is to analyze the data collected from this program using Interview analysis. The results of legal counseling at SMPN 1 Haurgeulis show that the role of the School Committee and Teachers is very important in preventing juvenile delinquency. Various factors from families and non-families contribute to child crime, so strengthening the role of the School Committee is relevant in the diversion strategy. School and Teacher Committees have a crucial role in efforts to prevent and diversion children's crimes. Therefore, the empowerment of the Committee and the implementation of diversion strategies need to be continuously improved so that children who are faced with the law can continue their education and have a better future.